Synthesis, analysis and photocatalysis of AgBr/Bi2MoO6nanocomposites - Sittikorn Jonjana (2018)
© 2016 Elsevier B.V. Heterostructure AgBr/Bi2MoO6nanocomposites for visible-light-driven photocatalyst were synthesized by deposition-precipitation. Upon characterization the nanocomposites, cubic AgBr nanoparticles were detected to adsorb on orthorhombic Bi2MoO6nanoplates. Effect of AgBr contents on photodegradation of rhodamine B (RhB) under visible white light was investigated. The 10 wt% AgBr/Bi2MoO6nanocomposites exhibited the highest photocatalytic activity of 97% within 40 min. A mechanism for photodegradation of RhB by AgBr/Bi2MoO6nanocomposites was also discussed.